Evaluation of the bioavailability of hydrocortisone when prepared as solid dispersion - Mohammad A. Altamimi; Ehab M. Elzayat; Wajhul Qamar; Sultan M. Alshehri; Abdelrahman Y. Sherif; Nazrul Haq; Faiyaz Shakeel (Elsevier, 2019)
This study was conducted to formulate, characterize, and investigate the bioavailability of hydrocortisone (HCT) when prepared as solid dispersions. HCT was mixed in an organic solvent with polyethylene glycol 4000 (PEG 4000) and Kolliphor® P 407. Spray drying technique was employed to form a solid dispersion formulation at a specific ratio. Physical and chemical characterization of the formed particles were achieved using differential scanning calorimetry, scanning electron microscopy, Fourier transform infrared spectroscopy, and powder X-ray diffractometry. Furthermore, comparative in vitro and in vivo studies were conducted between the formulated particles against neat HCT. The formulated solid dispersion showed elongated particles with leaf-like structure. Formation of new chemical bonds in the formed particle was suggested due to the change in the vibrational wave numbers and the significant improvement in the bioavailability of the dispersed particles proved the importance of this technique. Keywords: Hydrocortisone, Solid dispersion, Spray drying, Low potency, Bioavailability, PEG 4000, Kolliphor® P 407